2013
DOI: 10.7448/ias.16.1.18023
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk human papillomavirus infection in HIV‐positive African women living in Europe

Abstract: IntroductionCervical infection with high-risk human papillomavirus (HRHPV) induces cervical cancer and is present in 14% of women in Europe. We assessed the prevalence and incidence of cervical HRHPV in a cohort of HIV-positive women living in Belgium.MethodsProspective observational program of screening and follow up of HRHPV cervical infection performed by Hybrid Capture in 825 HIV-positive women between 2002 and 2011. Women without normal cervix at baseline were excluded.ResultsThe final analysis included 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28]. Furthermore, previous reports showed that HIV-infected women had a seven-fold increased rate of persistence of HR-HPV [29].…”
Section: Discussionsupporting
confidence: 80%
“…These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28]. Furthermore, previous reports showed that HIV-infected women had a seven-fold increased rate of persistence of HR-HPV [29].…”
Section: Discussionsupporting
confidence: 80%
“…A follow-up to that study will determine whether precancerous lesions were missed on cytology smears in these women. A prospective longitudinal study of a large cohort of 652 HIV-infected women primarily of African origin but living in Belgium and with normal cervical cytology had similar findings (185). The prevalence of high-risk HPV infection at first screen was 42.8%, with the majority of positive results occurring in women under age 30 and in those with CD4 counts less than 200 cells/l but with prevalence remaining higher than in the general population across each age and CD4 count group.…”
Section: High-risk Hpv Detection As a First-line Test In Primary Cervmentioning
confidence: 66%
“…These factors contribute to the finding that HIV-infected women are three to five times more likely than HIVuninfected women to develop cervical dysplasia (183). HPV prevalence in HIV-infected populations is more than three times the estimated prevalence of 12% found in the general population and ranges from about 31% to 57%, with higher percentages in Africa than in North America or Western Europe (185). A pilot study conducted in Jos, Nigeria, evaluated a cohort of 97 HIV-infected women age 21 to 49 with normal cytology (186).…”
Section: High-risk Hpv Detection As a First-line Test In Primary Cervmentioning
confidence: 91%
“…HPV infection, especially by HPV-16, has been commonly identified as a risk factor contributing to the onset of head and neck cancers, predominantly those of the oropharynx, tonsils, and the base of the tongue [31]. A recent cohort study found that the relative risk of carrying HPV decreased proportionately by 11% for each 100 CD4 cells/μL increase, suggesting plausible co-infection of HPV in immunosuppressed including HIV-positive individuals, as well as attenuating risk of HPV infection with improved immune function [37]. The large number of HIV-positive head and neck cancer cases in this study may be due to this co-infection, though more complete HPV status data in ORCI medical records will be necessary to confirm this association.…”
Section: Discussionmentioning
confidence: 99%